2014
DOI: 10.1111/jcpp.12281
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of early language development to children's emotional and behavioural functioning at 6 years: an analysis of data from the Children in Focus sample from the ALSPAC birth cohort

Abstract: Background An association between children's early language development and their emotional and behavioural functioning is reported in the literature. The nature of the association remains unclear and it has not been established if such an association is found in a population‐based cohort in addition to clinical populations. Methods This study examines the reported association between language development and emotional and behavioural functioning in a population‐based cohort. Data from 1,314 children in the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
3
43
0
2
Order By: Relevance
“…Children with early language problems have higher rates of behavioral and emotional difficulties later in childhood compared to other children (Beitchman et al., ; Tomblin, Zhang, Buckwalter, & Catts, ). The majority of the evidence has focused on clinical samples using clinical cut‐points, but evidence from the general population and in studies considering the full range of functioning have also found consistent associations (Bretherton et al., ; Clegg, Law, Rush, Peters, & Roulstone, ; Tomblin et al., ). Nevertheless, despite one in five children having problems in one or more of these development domains (Reilly et al., ), the association between language and subsequent behavioral and emotional difficulties is poorly understood.…”
Section: Change In Language and Behavioral And Emotional Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with early language problems have higher rates of behavioral and emotional difficulties later in childhood compared to other children (Beitchman et al., ; Tomblin, Zhang, Buckwalter, & Catts, ). The majority of the evidence has focused on clinical samples using clinical cut‐points, but evidence from the general population and in studies considering the full range of functioning have also found consistent associations (Bretherton et al., ; Clegg, Law, Rush, Peters, & Roulstone, ; Tomblin et al., ). Nevertheless, despite one in five children having problems in one or more of these development domains (Reilly et al., ), the association between language and subsequent behavioral and emotional difficulties is poorly understood.…”
Section: Change In Language and Behavioral And Emotional Difficultiesmentioning
confidence: 99%
“…We will test associations separately for the whole group of children, and then for children below the 50th percentile for vocabulary at age 4-5 years. Given research showing associations between vocabulary and behavioral and emotional problems in both clinical and population groups (Bretherton et al, 2014;Clegg et al, 2015;Tomblin et al, 2000), we expected associations to be consistent for the whole sample compared to children in the lower 50th percentile for language at 4-5 years.…”
Section: The Current Studymentioning
confidence: 99%
“…), educational attendance (HM Government and Ministry of Justice ) and non‐verbal intelligence (IQ) (Clegg et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of cohort data has identified non‐verbal IQ as a correlate of emotional and behavioural outcomes (Clegg et al . ) and non‐verbal IQ is still recognized as a correlate of language ability (Wetherell et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Vocabulary knowledge is a foundational skill of meaning making and, in typically developing children, has been found to be predictive of both literal and inferential verbal comprehension (Silva & Cain, ), reading comprehension (Ouellette & Beers, ), and behavioral functioning (Clegg, Law, Rush, Peters, & Roulstone, ). Similar associations have been identified for individuals with Down syndrome (DS), with receptive vocabulary being a predictor of academic outcomes including spelling (Lim, Arciuli, Liow, & Munro, ) and reading (Laws & Gunn, ), and of social skills (Hippolyte, Iglesais, Van der Linden, & Barisnikov, ).…”
Section: Introductionmentioning
confidence: 99%